2020
DOI: 10.3390/jcm9092744
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Stewardship Program, COVID-19, and Infection Control: Spread of Carbapenem-Resistant Klebsiella Pneumoniae Colonization in ICU COVID-19 Patients. What Did Not Work?

Abstract: The Italian burden of disease associated with infections due to antibiotic-resistant bacteria has been very high, largely attributed to Carbapenem-Resistant Klebsiella pneumoniae (CR-Kp). The implementation of infection control measures and antimicrobial stewardship programs (ASP) has been shown to reduce healthcare-related infections caused by multidrug resistance (MDR) germs. Since 2016, in our teaching hospital of Terni, an ASP has been implemented in an intensive care unit (ICU) setting, with the “daily-IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
131
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 19 publications
4
131
1
3
Order By: Relevance
“…Moreover, we postulated a negative impact of COVID-19 on antimicrobial stewardship programs, an issue reported in a speculative manner in various reviews and editorials. To the best of our knowledge, only one real-life report describes the acquisition of CR-Kp colonization among COVID-19 patients [15], while two centers reported an increase in C. auris infections in COVID-19 patients [16,17]. We supposed that the main drivers of an increase in antimicrobial resistance during COVID-19 in our hospital were the use of broad-spectrum antimicrobials and horizontal spread of resistant strains.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, we postulated a negative impact of COVID-19 on antimicrobial stewardship programs, an issue reported in a speculative manner in various reviews and editorials. To the best of our knowledge, only one real-life report describes the acquisition of CR-Kp colonization among COVID-19 patients [15], while two centers reported an increase in C. auris infections in COVID-19 patients [16,17]. We supposed that the main drivers of an increase in antimicrobial resistance during COVID-19 in our hospital were the use of broad-spectrum antimicrobials and horizontal spread of resistant strains.…”
Section: Discussionmentioning
confidence: 88%
“…In this sense, a retrospective observational study analysed the bimonthly incidence of carbapenem-resistant Enterobacteriaceae (CRE) colonisation and the incidence of CRE acquisition in an Italian intensive care unit from January 2019 to June 2020 and reported that the incidence of CRE acquisition went from 6.7% in 2019 to 50% in March–April 2020. Authors stated that the high intensity of care, the need to be changed in a prone position and prolonged contact with the patient, and the presence of health personnel without work experience in intensive care setting contributed to the spread of CRE acquisition [ 29 ]. In our centre, the incidence and death rates of hospital-acquired candidemia and MDR bacterial BSI showed a stable trend and, moreover, the quality of care measured by the percentage of deaths in patients diagnosed with BSI did not deteriorate.…”
Section: Discussionmentioning
confidence: 99%
“…Experience from a teaching hospital that has implemented antimicrobial stewardship measures at an ICU with special attention on infection control measures, the carbapenem-resistant Enterobacteriaceae incidence rose from 6.7% in 2019 to up to 50% in March and April of 2020. Obviously, with staff training and implementation of the antimicrobial stewardship measures, a reduction in carbapenem-resistant Enterobacteriaceae was expected [ 76 ].…”
Section: Antibiotic Prescribing For Covid-19 and The Unnecessary Umentioning
confidence: 99%